THE PROFILE OF STUDENT ACTIVITIES IN LEARNING BASIC NATURAL SCIENCE CONCEPTS THROUGH THE CONTEXTUAL TEACHING AND LEARNING (CTL) APPROACH WITH GROUP INVESTIGATION (GI) MODEL - Chusni, Muhammad Minan; Mahardika, Astuti; Sayekti, Ika Candra; Setya, Winda (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2017)
Abstract Science learning essentially requires students to cultivate curiosity so that it triggers to conduct investigations by doing science activities. The purpose of this research is to know the profile of student activity in learning basic concept of IPA through contextual teaching and learning approach (CTL) with group investigation (GI) model.The subject of this research is Program of primary teacher education UMMGL students consisting of two classes with 83 people. The research method is descriptive. Data collection techniques were conducted by setting the focus of research, selecting informants as data sources, collecting data, assessing data quality, analyzing data, interpreting data, and drawing conclusions on the findings.From the research results can be concluded that the profile of student activity in learning basic concept of science through CTL approach with the average GI model is in very good category. Keywords: Activity, CTL, GI, Science Learning Essentially